PERBANDINGAN ANGKA KEJADIAN TBC PADA ANAK USIA 10-14 TAHUN DENGAN RIWAYAT IMUNISASI Bacillus Calmette-Guerin dan NON-BCG - Kk Noveriansyah Eka Putra Nksrsb (2020)
Tuberculosis is one of the highest causes of death in the world besides upper respiratory infections and cardiovascular disease. In the world, tuberculosis sufferers number between 9 million to 11.1 million people with the highest incidence in tropical and sub-tropical regions such as Indonesia. Tuberculosis infection can threaten the lives of sufferers, but there is one way to prevent tuberculosis by immunizing BCG. BCG immunization can prevent hematogenous spread of tuberculosis bacteria This study aims to compare the incidence of tuberculosis in children aged 10-14 years with a history of BCG and non-BCG immunization. This study used a descriptive categorical research design with a sample of children aged 10-14 years who were diagnosed with tuberculosis and immunization history obtained from Fatmawati General Hospital 2017-2019. The results of this study were found in environments with high BCG immunization status, the growth of tuberculosis bacteria only in the lungs and did not complicate into more severe tuberculosis.